Literature Review: Penerapan Project-Based Learning terhadap Pembelajaran Inovatif IPA - Nurfitra Yanto; Rifda Nur Hikmahwati Arif; Sakinah Zubair (Lembaga Bale Literasi, 2025)
Twenty-first century science education demands instructional approaches that simultaneously develop conceptual understanding and applied skills. This study aims to analyze the implementation of Project-Based Learning (PjBL) in science education through a systematic literature review. The research method involved rigorous analysis of 20 peer-reviewed articles published between 2017 and 2024, selected through strict inclusion and exclusion criteria. The analysis revealed three key findings: (1) PjBL effectively enhances student engagement and conceptual understanding in science learning; (2) the model significantly contributes to the development of 21st-century skills, particularly critical thinking, collaboration, and scientific literacy; (3) PjBL demonstrates high compatibility with the investigative and contextual nature of science education. The study concludes that PjBL represents an innovative and effective approach for improving science education quality across various educational levels. These findings recommend the development of more operational PjBL implementation guidelines to better support educators in optimally applying this model.